Indigenous women, justice and rights: challenges for an intercultural justice - Sierra, María Teresa (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2008)
Community and indigenous forms of justice face not only racism and exclusion of state’s justice, but the challenges related with diversity acknowledge policies. The article presents two cases of indigenous justice in Mexico, which allow to examine the ways that gender and human rights demands clash with ideologies embeded in this kind of legal practices. If these practices tend to naturalize women exclusion, on the other hand, it is showed how women in this process contribute to question the traditional justice practices by redefining their own cultural frames.